Digitalisasi Pariwisata Melalui Variasi Bahasa Konten Kreator Kelurahan Wonolopo Kecamatan Mijen Kota Semarang - Sony Junaedi; Hadi Karyono; Eni Purwanti (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Implementing this Community Service Program strengthens the digitalization of tourism by accelerating the herbal medicine village tourism village based on the language variations of content creators. Currently, not many tourists and enthusiasts come to buy herbal medicine at Kampung Jamu Wonolopo. Based on this description, the Community Service Team of the University of 17 Agustus 1945 Semarang assists Mitra Pokdarwis Manggar Selaras, which includes activities: Socialization and Program Coordination with Partners, Motivation and Strengthening HR Capacity, Training and Practice in Using Tools for Creating Digital Content, Workshop on Creating and Editing Video Content, Workshop on Using Various Languages for Content Creators, Handing Over Appropriate Technology Tools. As a result of this service, it is hoped that the residents of Jamu Wonolopo village will be able to improve the quality of human resources through digital skills to manage the development of the tourism potential of Jamu village by optimizing the preservation of nature and culture through interesting language variety content, to improve the quality of life for economic growth, job creation so that The results can improve community welfare.